Will healthy diets increase household food waste? - Cao, Xue; Li, Xu (Frontiers in Sustainable Food Systems, 2023)
With rapid changes in Chinese society, people's health awareness is also increasing fast, and diets have transitioned from the pursuit of "filling up" to "being well-fed" to today’s "eating reasonably and healthily." How does this change in healthy diet awareness affect household food waste? Based on a theoretical analysis of the relationship between healthy eating awareness and household food waste, this study uses data from the China Health and Nutritional Survey（CHNS） to further investigate the issue. This study is the first to view household food waste from the perspective of healthy diet awareness and propose a theoretical framework of the effects of healthy diet awareness. The results show that greater awareness of what constitutes a healthy diet can significantly reduce household food waste. Household size, family population structure, income, and the employment status of the household’s main female member are important explanatory variables. We believe government support for advocating and publicizing healthy diets will help reduce household food waste.